DASAR-DASAR MANAJEMEN KEUANGAN DAN EDUKASI MENGENAI PENDIDIKAN BERKELANJUTAN BAGI MILENIAL DALAM MENCIPTAKAN PELUANG DI ERA DIGITAL - Mufahamah, Euis; Rahyono, Rahyono; Muhammad, Muhammad; Harun, Harmani; Wicaksono, Fardan Abi; Magad, Azidan; Putri, Addela Mariska (Program Studi Manajemen Fakultas Ekonomi dan Manajemen Universitas Malahayati, 2024)
The purpose of the study is to identify the role of education in disseminating social and economic values. The assessment is a field research that uses a qualitative approach to obtain information about programs developed by millennials, as well as their application in educational units which include targets and are instilled in educational units, most of them still focus on environmental perspectives and various program objectives, most of the program targets are educators, students and school principals; strategies for instilling various values, namely through integration into subjects, through local content, extracurriculars, habituation and acculturation, as well as other activities, which are mostly carried out, namely through integration and habituation and acculturation.